Building Democracy In Latin America: United States Foreign Aid For Haiti - Arindrayani, Angelica (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
This article provides an overview, implications, and challenges that arise at the intersection of international political, economic, social, and environmental dilemmas that intervened in Haiti's efforts to build the stability of its democracy during the pre-Cold War period until recently. By providing United States Agency for International Development (USAID)'s trend of democratic assistance to the Latin American region and the presidential leadership model that may explain Haiti's failure to combat political instability, this article has positioned the Haitian government as a contributor to Haiti's permanent crisis, with the role of an elite society taking control of the interim government system and the civil society as the party to bear the consequences. The occurrence of a devastating earthquake has tested Haiti and resulted in more and more Haitians migrating to the United States. This condition exacerbated Haiti's status as a